The Epidemiology of Depressive Symptoms in the Last Year of Life - Kozlov, Elissa (J Am Geriatr Soc, 2019)
BACKGROUND/OBJECTIVE: Depression impacts quality of life at all life stages, but the epidemiology of depression in the last year of life is unknown. This study’s objectives were to document the epidemiology of depressive symptoms in the year prior to death and to assess how the trajectory of depressive symptoms varies by sociodemographic and clinical factors. DESIGN: Observational, cross-sectional, cohort study using the Health and Retirement Study. SETTING: Population-based survey. PARTICIPANTS: A total of 3274 individuals who died within 12 months after assessment. MEASURES: Primary outcome: eight-item Center for Epidemiologic Studies Depression Scale (CESD-8). Covariates included sociodemographics, self-reported illnesses, and activity of daily living (ADL) limitations. RESULTS: Average CESD-8 score increased over the last year of life, with 59.3% screening positive for depression in the last month before death. Depression symptoms increased gradually from 12 to 4 months before death (increase of 0.05 points/month; 95% confidence interval [CI] = 0.01–0.08 points/month) and then escalated from 4 to 1 months before death (increase of 0.29 points/month; 95% CI = 0.16–0.39 points/month). Women, younger adults, and nonwhite adults all demonstrated higher rates of depressive symptoms. Individuals with cancer reported escalating rates of depressive symptoms at the end of life, while individuals with lung disease and ADL impairment demonstrated persistently high rates throughout the year before death. CONCLUSIONS: This study revealed high rates of depressive symptoms in the last year of life as well as differences in the burden of depressive symptoms. A public health approach must be taken to screen for and appropriately treat symptoms of depression across the lifespan.